Lucian Freud's painterly-pictorial translation of perceived reality : a study that bears relation to my own painting - Menck, Clare,1969- (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Sc.) -- University of Stellenbosch, 1997.